2022
DOI: 10.3389/fimmu.2022.994888
|View full text |Cite
|
Sign up to set email alerts
|

Decidual macrophages in recurrent spontaneous abortion

Abstract: Recurrent spontaneous abortion (RSA) is defined as two or more pregnancy loss, affecting the happiness index of fertility couples. The mechanisms involved in the occurrence of RSA are not clear to date. The primary problem for the maternal immune system is how to establish and maintain the immune tolerance to the semi-allogeneic fetuses. During the pregnancy, decidual macrophages mainly play an important role in the immunologic dialogue. The purpose of this study is to explore decidual macrophages, and to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 123 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…It has been fully elucidated that decidual macrophages contribute the second largest decidual leukocyte population at the maternal-foetal interface in the first trimester, next to natural killer cells [ 4 ]. Emerging evidence has indicated an association between the disturbance of decidual macrophages and the occurrence of RSM [ 2 ]. Our current study sought to integrate DNA methylation data with transcriptome profiles to explore key epigenetic features in decidual macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been fully elucidated that decidual macrophages contribute the second largest decidual leukocyte population at the maternal-foetal interface in the first trimester, next to natural killer cells [ 4 ]. Emerging evidence has indicated an association between the disturbance of decidual macrophages and the occurrence of RSM [ 2 ]. Our current study sought to integrate DNA methylation data with transcriptome profiles to explore key epigenetic features in decidual macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent spontaneous miscarriage (RSM) refers to two or more consecutive spontaneous abortions with the same spouse before the 20th week of gestation [ 1 ]. RSM accounts for approximately 2–5% of the total pregnancies [ 2 ]. Although concentrated research has identified numerous causes of RSM, such as chromosomal abnormalities, abnormal reproductive structure, endocrinopathies, and thrombophilic disorders, 50% of RSM cases are still unexplained [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…DMφ, characterised by M2-like macrophages, are integral components of decidual immune cells at the maternal-fetal interface, crucial for maintaining maternal-fetal tolerance and trophoblast invasion [29]. The removal of macrophages in pregnant rats results in abortions, highlighting their signi cance in sustaining normal pregnancies [16,30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results suggested that NCK1 may regulate PD-L1-mediated macrophage proliferation. Previous studies have reported that RM was closely associated with immune dysfunction, such as imbalance of macrophage polarization and dysfunction of macrophage cytokine secretion ( Zhao et al, 2022 ). Thus, enhanced proliferation of macrophages may be detrimental to pregnancy maintenance by causing immune dysfunction at the maternal-fetal interface.…”
Section: Discussionmentioning
confidence: 99%